Effect of treatments and washing cycles on the quality of Nile tilapia (Oreochromis niloticus) protein concentrate - Lígia Boarin Alcalde; Ângela Dulce Cavenaghi-Altemio; Gustavo Graciano Fonseca (Journal of Fisheries, 2017)
The extraction of proteins from wastes reduces production costs and environmental pollution. The aim of this work was to evaluate the effect of two treatments involving decanting/sieving or centrifugation and the number of washing cycles on the quality of protein concentrate obtained from mechanically separated meat (MSM) of Nile tilapia (Oreochromis niloticus). Results were analyzed in terms of final yield and proximate composition (moisture, protein, fat and ash) after each washing cycle. Moisture did not vary statistically with the treatments and after the third washing cycle. However, the process involving centrifugation was more efficient for protein concentration because the final protein content increased 2.0 folds (79.82%, dry basis) and fat decreased 6.1 folds (8.29%, dry basis). After four washing cycles, it was obtained a protein concentrate with 79.82% protein, 8.29% lipid and 0.45% ash (dry basis), and 80.0% yield, using the centrifugation procedure. Visual whiteness was highly improved after four washing cycles using both processes. It was concluded that the centrifugation process with four washing cycles was the most appropriate method for producing protein concentrate from MSM of Nile tilapia.